2016
DOI: 10.1089/neu.2015.4362
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sensor Technology To Assess Independence and Limb-Use Laterality in Cervical Spinal Cord Injury

Abstract: After spinal cord injury (SCI), levels of independence are commonly assessed with standardized clinical assessments. However, such tests do not provide information about the actual extent of upper limb activities or the impact on independence of bi- versus unilateral usage throughout daily life following cervical SCI. The objective of this study was to correlate activity intensity and laterality of upper extremity activity measured by body-fixed inertial measurement units (IMUs) with clinical assessment scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In agreement with our previous study (31), these two categories were distinguished based on the output of the RSWA (set-up II.a). The category “self-propulsion AC” included all upper extremity movements performed while the subject actively propelled the wheelchair, whereas the category “ADL AC” included all upper extremity movements that occurred during any other day-to-day activities excluding self-propulsion.…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…In agreement with our previous study (31), these two categories were distinguished based on the output of the RSWA (set-up II.a). The category “self-propulsion AC” included all upper extremity movements performed while the subject actively propelled the wheelchair, whereas the category “ADL AC” included all upper extremity movements that occurred during any other day-to-day activities excluding self-propulsion.…”
Section: Methodssupporting
confidence: 85%
“…This is because we have previously shown that paraplegic subjects do not show any limb-use laterality (22) and their limb-use laterality indexes are similar to healthy subjects (43). In analyzing only the lateralized-group, we showed that lateralized cervical subjects significantly decreased limb-use laterality but remained impaired with limb-use laterality values in the same range as a group of chronic tetraplegic subjects who we measured previously (31). …”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In a group of 16 subjects with a cervical lesion level, it was shown, that most subjects reported a stronger side and differences in maximal voluntary contraction between contralateral sides in upper extremities (21). Furthermore, a laterality toward one body side was seen in individuals with tetraplegia during activity (22). Thus, it seems important to have a look for UEMS and MIL in the medical history of athletes with a tetraplegia before interpretation of the results.…”
Section: Body Composition In Able-bodied and Disabled Athletesmentioning
confidence: 99%